2022
DOI: 10.1021/acsbiomaterials.1c01099
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Tumor Spheroid-on-a-Chip Model Verifies Synergistic Vasoprotective and Chemotherapeutic Effects

Abstract: Prolyl hydroxylases (PHD) inhibitors have been observed to improve drug distribution in mice tumors via blood vessel normalization, increasing the effectiveness of chemotherapy. These effects are yet to be demonstrated in human cell models. Tumor spheroids are three-dimensional cell clusters that have demonstrated great potential in drug evaluation for personalized medicine. Here, we used a perfusable vascularized tumor spheroid-on-a-chip to simulate the tumor microenvironment in vivo and demonstrated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…The different relative sizes between tumor and vascular tissue in these three models mimic the interaction between tumor and blood vessels at different stages of cancer. A vascularized tumor spheroid-on-a-chip model was developed by Ma’s group to verify synergistic vasoprotective and chemotherapeutic effects ( Figure 4 (Ab)) [ 129 ]. They constructed a perfusion–perfused vascularized tumor spheroid-on-a-chip model.…”
Section: Ooc For Tumor Modelingmentioning
confidence: 99%
“…The different relative sizes between tumor and vascular tissue in these three models mimic the interaction between tumor and blood vessels at different stages of cancer. A vascularized tumor spheroid-on-a-chip model was developed by Ma’s group to verify synergistic vasoprotective and chemotherapeutic effects ( Figure 4 (Ab)) [ 129 ]. They constructed a perfusion–perfused vascularized tumor spheroid-on-a-chip model.…”
Section: Ooc For Tumor Modelingmentioning
confidence: 99%
“…To construct vessels with a diameter smaller than 100 μm, the second method, based on endothelial cell self-assembly in hydrogels, has been reported. After being seeded into hydrogels at appropriate concentrations, endothelial cells can deform and self-assemble into interconnected and perfusable capillary networks. ,,, This approach has been broadly used to build vascularized tissue models on-chip in the last decades. , For example, Offeddu et al reported their work on building a breast cancer metastasis model with this approach and evaluated the role of endothelial cell glycocalyx in tumor cell metastatic extravasation . Furthermore, by providing mechanical and biochemical cues in the hydrogels on such platforms, endothelial cells can migrate and sprout in the hydrogel to form new vessels. ,,, Kim et al demonstrated that the endothelial cells could sense both interstitial flow and growth factor gradient, thus sprout to form new vessels against the flow direction and the growth factor gradient in hydrogel. , Nashimoto et al show that the vascularized tumor model can be constructed by inducing angiogenesis with the spheroids consisting of fibroblasts and tumor cells in hydrogel …”
Section: Introductionmentioning
confidence: 99%
“…Nashimoto et al combined spheroid culture (formed of lung fibroblasts and HUVECs) with angiogenesis strategies by culturing the spheroid together with endothelial cells in a microfluidic device [13]. Hu et al also produced a perfusable vascularised tumor spheroid by adding it to a microvascularised microfluidic chamber and showing integration between the two structures [14]. Although the number of studies reporting integrated microvascularised tissue models is rapidly increasing, there is a need to increase the range of tissues that can be integrated with microvascularised networks, without impacting their structural and functional performance.…”
Section: Introductionmentioning
confidence: 99%